Editorial: Special issue: Land Use Transport Interaction Modelling - Geurs, Karst; Ritsema van Eck, Jan (European Journal of Transport and Infrastructure Research, 2004)
That land-use and transport systems are interdependent and characterized by a two-way interaction is a well-known fact. The spatial configuration of activities influences the level and characteristics of transportation demand, and conversely, the location and quality of transportation infrastructure affects how activities are organized in space. Since the 1960s, several methodologies and models have been developed and used to examine the land-use and transport patterns and change. The research issues addressed using these models have, since the 1990s, been broadened to include sustainability impacts in transport policy, thereby strongly increasing modelling demands and raising several research challenges. This was the theme of a special session on ‘Land Use Transport Interaction Modelling and Sustainability’, as part of the international conference ‘Framing Land Use Dynamics’ held in April 2003 at Utrecht University (UU) in the Netherlands. The conference was organised as part of the Utrecht University’s multidisciplinary research programme, ‘Networks in the Delta’, aimed at developing a theoretical and methodological framework for understanding and modelling the complex interactions between socio-economic and environmental systems (see website Networks in the Delta (2004) for a full description). The papers included in this special issue of the European Journal of Transport and Infrastructure Research were presented at the conference under the theme, ‘Infrastructure, mobility and land-use planning’, focusing on transportation and land-use dynamics. Papers describe experiences with land-use and transport interaction models as impact assessment and policy appraisal tools, with contributions covering different local, regional and national spatial scales in Western European contexts, in particular, the United Kingdom, Germany and the Netherlands.